2021
DOI: 10.1155/2021/7532905
|View full text |Cite
|
Sign up to set email alerts
|

The Readability of Patient Education Materials Pertaining to Gastrointestinal Procedures

Abstract: Introduction. Due to the ubiquity and ease of access of Internet, patients are able to access online health information more easily than ever. The American Medical Association recommends that patient education materials be targeted at or below the 6th grade level in order to accommodate a wider audience. In this study, we evaluate the difficulty of educational materials pertaining to common GI procedures; we analyze on the readability of online education materials for colonoscopy, flexible sigmoidoscopy, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Numerous studies have been published assessing the readability of patient education materials, with a staggering trend towards texts written above the recommended grade level. [11][12][13][14][15][16][17][18][19][20][21][22] Our online queries yielded an average readability level that greatly surpassed the recommended 6th grade reading level set by the NIH and the AMA. Among the four different readability formulas, the lowest average readability level was equivalent to an 11th grade reading level.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Numerous studies have been published assessing the readability of patient education materials, with a staggering trend towards texts written above the recommended grade level. [11][12][13][14][15][16][17][18][19][20][21][22] Our online queries yielded an average readability level that greatly surpassed the recommended 6th grade reading level set by the NIH and the AMA. Among the four different readability formulas, the lowest average readability level was equivalent to an 11th grade reading level.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 78%
“…Although a few patterns have been published regarding the difficult readability of non-profit websites, when examining the multitude of readability analyses, no clear trend emerges. [11][12][13][14][15][16][17][18][19][20][21][22] The Urology Care Foundation, a non-profit webpage, stands out as one of the lowest scored pages and thus was easily comprehensible. In a similar study, Routh et al compared internet sources between common and uncommon pediatric urology topics and found that webpages on uncommon topics like exstrophy had inferior accuracy and completeness.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
“…Indeed, this challenge is not unique to the information on CBE nor that of urology, it is endemic to all fields of medicine. Countless studies have been published evaluating the readability of patient education materials online across multiple specialties, and the trend for information to be above the recommended reading level is overwhelming (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Former studies of readability analysis in other fields were employed as methods for this study [13,14]. The topics of patient preparation, procedure, postoperative care, and complications with regard to esophageal dilation were established, and subsequent keywords were developed to encompass these topics.…”
Section: Evaluating Readability and Keyword Rationalementioning
confidence: 99%